2005
DOI: 10.1093/eurheartj/ehi447
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness of heart failure in Europe: first results from SHAPE

Abstract: In Europe, community awareness of HF is low. Therefore, the general public is unlikely to demand appropriate measures by healthcare authorities and providers. A better understanding of HF could improve its prevention and management. Strategies to educate the public about HF are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
100
0
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 22 publications
11
100
0
12
Order By: Relevance
“…These results were comparable to earlier studies,2, 4 although the percentage of respondents, who knew all three main symptoms of HF, has strongly increased from only 3% reported for the 912 Germans from the population‐based survey study SHAPE conducted in 20022 to 39% in our study. This huge increase in percentage may also partially stem from a selection bias, as people in the present study can be suspected to be interested in health issues and were picked on a health information event at a university.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results were comparable to earlier studies,2, 4 although the percentage of respondents, who knew all three main symptoms of HF, has strongly increased from only 3% reported for the 912 Germans from the population‐based survey study SHAPE conducted in 20022 to 39% in our study. This huge increase in percentage may also partially stem from a selection bias, as people in the present study can be suspected to be interested in health issues and were picked on a health information event at a university.…”
Section: Discussionsupporting
confidence: 92%
“…Such variables could be unevenly distributed in the populations at the different time points and therefore have a stronger or slighter impact in different years' populations, biasing the results. Indeed, although similar to the German population regarding the distribution of age and gender, a greater proportion of our sample had higher education, worked in a medical profession, and were more frequently affected by HF 2, 19, 20, 21, 22, 23…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A survey in nine European countries (SHAPE, 2005) exploring general awareness about heart failure has shown that out of almost 8000 inhabitants only 3% could identify heart failure from a description of the symptoms and signs; although, 31% of subjects could identify angina and 51% stroke [18].…”
Section: Epidemiologic Considerationsmentioning
confidence: 99%
“…Only 3% of respondents correctly identified heart failure from a description of typical signs and symptoms ("breathlessness, tiredness, or swollen ankles") in the Study of Heart Failure Awareness and Perception in Europe (SHAPE) survey of almost 8000 people in nine European countries. 81 By contrast, 28% identified heart attack/ angina and 48% identified stroke or its equivalent from a description. Moreover, only 29% of respondents considered heart failure "a severe complaint" based on the description of signs and symptoms, and 34% perceived it to be "a normal consequence of getting older".…”
mentioning
confidence: 98%